CHALLENGES OF INFORMATION TECHNOLOGIES INTEGRATION INTO STUDY PROCESS: TEACHERS’ PERSPECTIVE - Tereseviciene, Margarita; Miskiniene, Birute; Tamoliune, Giedre (European Scientific Journal, ESJ, 2014)
Modern university teachers are expected to have competences to organise e-learning activities; also, they should be ready to integrate information technologies (further – IT) into everyday teaching and learning processes. Teachers’ preparation to use IT helps to improve teaching and learning quality and to expand scientific activities into other academic fields. The question of IT usage and its necessity in educational institutions has been widely discussed in recent years. Still it is important to analyse how teachers succeed while integrating IT into their study process, what challenges they usually face and how higher education institutions (further – HEI) support the need to improve teachers’ IT competences. These are the main questions discussed in this article. The theoretical part of the article provides a brief presentation of a variety of concepts used while discussing the topic of IT integration in learning process and points out the main challenges that teachers might face during this process. Research results have demonstrated that there is lack of clearly defined IT competences and there is no periodical evaluation system of these competences. From the practical perspective, university teachers have noted lack of guidelines for some technological solutions.